(untitled) (Plant Tissue Culture and Biotechnology, 2011)
identified unequivocally. Putative microbial pathogens (fungi and bacteria) were studied in dieback affected sissoo trees collected from Bangladesh, using plant pathological techniques combined with molecular tools. DNA based characteri-zation showed the presence of heterogeneous patterns of various fungi (mostly saprophytic). It did not support the hypothesis of Fusarium solani being the cause of sissoo dieback. In contrast, isolation and molecular characterisation of bacteria from dieback affected sissoo revealed the presence of Pseudomonas in 83% of the samples. Sequencing the gene of 16S ribosomal RNA, the rpoD-gene, the gacA-gene and the rnpB-gene strongly suggested that these isolates belong most probably to a still unassigned Pseudomonas species. Hypersensitivity response assays and infection studies using sissoo seedlings demonstrated their pathogenic potential. Key words: Sissoo, dieback, Pseudomonas, fungal pathogens D.O.I. 10.3329/ptcb.v21i2.10214 Plant Tissue Cult. & Biotech. 21(2): 101-113, 2011 (December)